TRANSFORMATION OF EDUCATIONAL STYLES IN THE EDUCATIONAL SYSTEM OF ISLAMIC BOARDING SCHOOLS, FROM TRADITIONAL PATTERNS TO MODERN PATTERNS - Fitrotun Ni'mah dan Ashif Az Zafi (LPPM IAI QOMARUDDIN GRESIK, 2021)
Pesantren is one of the oldest education systems in Indonesia, there are 6 aspects that must be owned by the Islamic Boarding School education system that wants to change according to the demands of the times. This research includes qualitative research and case studies. In this study, data were searched about the learning style of Islamic boarding schools in the modern era at Ponpes Matholi'ul Huda Jepara, the data collection techniques in this study were based on literature review, experience, and observations. This aspect is the educational aspect of the pesantren, the comparative analysis shows the fact that there are several aspects that have changed in the educational system of the Matholi'ul Huda pesantren. however, the changes occurred in technical aspects, such as gradation and curriculum, as well as in the aspect of the formalization of objectives. for the material aspect, the approach and learning model only experienced additions, meanwhile the educative interaction and the educational environment were still maintained. Keywords: Islamic boarding school, education aspect, Islamic boarding school education style, educational transformation